Successful allogeneic hematopoietic stem cell transplantation in a patient with type I CD36 deficiency: a case study and literature review - Okuyama, Shuhei; Sumi, Masahiko; Ishikawa, Ryuto; Shishido, Tsutomu; Koyama, Daisuke; Ueki, Toshimitsu; Takahashi, Daisuke; Kobayashi, Hironori; Kobayashi, Hikaru; Tsuno, Nelson Hirokazu (International journal of hematology, 2023)
Background CD36-deficient individuals may produce anti-CD36 antibodies through antigenic exposure to CD36, in situations including blood transfusions. Therefore, allogeneic hematopoietic stem cell transplantation (HSCT) from CD36-positive donors to CD36-negative patients remains a challenge. Case report A 64-year-old man with acute myeloid leukemia became refractory to platelet transfusions during chemotherapy. Anti-CD36 antibodies without anti-HLA antibodies were detected in serum, and the absence of CD36 expression on platelets and monocytes confirmed type I CD36 deficiency. The patient achieved complete remission, and received maintenance therapy with CD36-negative platelet transfusions. However, he relapsed soon afterward, and thus underwent peripheral blood stem cell transplantation (PBSCT) from a CD36-positive unrelated donor. The anti-CD36 antibody titer had decreased before the transplant, and the PBSCT-course was uneventful. The patient has been well without any complications associated with CD36 status mismatch. Discussion The few reports of allogeneic HSCT in patients with CD36 deficiency have suggested that anti-CD36 antibodies could be involved in several post-transplant complications, such as delayed platelet recovery, transfusion refractoriness, and transfusion-related acute lung injury. Our present case confirmed that stem cell transplantation from CD36-positive donors to negative patients is feasible, when it includes careful prior assessment of anti-CD36 antibody titers and interventions to attenuate them.